Electrochemical Study on the Reduction of Si and Ti from molten TiO2–SiO2–Al2O3–MgO–CaO Slag. Issue 6 (2nd June 2021) - Martin-Treceno, Samuel; Hughes, Thomas; Weaver, Nicholas; Marshall, Aaron T.; Watson, Matthew J.; Bishop, Catherine M.
Abstract : The reduction process during the electrochemical production of titanium via the electrolysis of molten TiO2 –SiO2 –Al2 O3 –MgO–CaO slags has been investigated. A laboratory scale, electrolytic cell was designed to study the effect of TiO2 concentration at ultra-high temperatures. Galvanostatic and potentiostatic experiments were performed and results were consistent with thermodynamic predictions using FactSage. We demonstrate the direct production of Si-Ti alloys from the molten oxide mixture. The reduction of Si and Ti ions from the melt on a molybdenum electrode is a complex process that combines electron transfer and chemical phenomena. For the concentrations studied, the extraction of pure metallic Ti directly from ironmaking slag is unlikely without the prior removal of SiO2 or other chemical modifications to the system.